A LEARNING RUSSIAN WITH DIGITAL TECHNOLOGIES: LEARNING RUSSIAN WITH DIGITAL TECHNOLOGIES - Kodirova, Kodirova G (Журнал иностранных языков и лингвистики, 2022)
This article shows the facilities of using digital technologies in Russian lessons. Such kind of technologies improve not only listening skills and also improve speaking skills. The author endeavors to show how important the digital technologies at the lessons and the active use of modern pedagogical technologies and digital technologies together, interactive forms of work increase the cognitive independence of teachers and students, motivate the need to develop their innovative culture.